Non-structure-specific intensity measure parameters and characteristic period of near-fault ground motions. - Yang, Dixiong (Earthquake engineering & structural dynamics.)
This paper focuses on the effects of long-period pulse of near-fault ground motions on the structural damage potential. Two sets of near-fault ground motion records from Chi-Chi, Taiwan earthquake and Northridge earthquake with and without distinct pulse are selected as the input, and the correlation analysis between 30 non-structure-specific intensity measure parameters and maximum inelastic displacements and energy responses (input energy and hysteretic energy) of bilinear single degree of freedom systems are conducted. Based on the frequency characteristic of near-fault ground motions with remarkable long-period components, two intensity indices are proposed, namely, the improved effective peak acceleration (IEPA) and improved effective peak velocity (IEPV). In addition a new characteristic period of these ground motions is defined based on IEPA and IEPV. Numerical results illustrate that the intensity measure parameters related to ground acceleration present the best correlation with the seismic responses for rigid systems; the velocity-related and displacement-related parameters are better for medium-frequency systems and flexible systems, respectively. The correlation curves of near-fault ground motions with velocity pulse differ from those of ground motions without pulse. Moreover, the improved parameters IEPA and IEPV of near-fault impulsive ground motions enhance the performance of intensity measure of corresponding conventional parameters, i.e. EPA and EPV. The new characteristic period based on IEPA and IEPV can better reflect the frequency content of near-fault ground motions.